Lexical and grammatical aspects of translating culture: a cognitive perspective - Stanojević, Mateusz-Milan (Array, 2006)
The aim of this paper is to use the non-objectivist tendencies of the communicative theory of translation as a starting point for the inclusion of cognitive elements into the communicative translation model. Out of the three crucial cognitive notions – the symbolic nature of grammar, aspects of construal and cultural models – we will be focusing on the last one, in an attempt to incorporate it into a coherent cognitive-communicative model. More specifically, we will argue that a broad view of cultural models (as opposed to a culture-specific view presented by communicative translation theories) can be profitable in providing a more systematic and cognitively-real view of translation.